Multiple electron capture from isolated protein poly-anions in collision with slow highly charged ions. Issue 30 (19th May 2017) - Milosavljević, A. R.; Rousseau, P.; Domaracka, A.; Huber, B. A.; Giuliani, A.
Abstract : Multiply charged ions very efficiently capture several electrons from trapped mass/charge selected protein poly-anions, producing dominantly charge-reduced proteins and small neutral losses. Abstract : Collisions of 375 keV Xe 25+ ions with trapped mass/charge selected poly-anions of the cytochrome C protein (∼12.5 kDa) were studied by coupling a linear quadrupole ion trap with low-energy ion beam facility. Tandem mass spectra were recorded for the protein precursor charge states ranging from −9 to −17. The present work reports the first study of slow highly charged ion collisions with poly-anions. A high signal to noise ratio allowed the study of the intensity of single and multiple electron removal by a projectile, as well as associated neutral losses, as a function of the target charge state. Relative single and double electron detachment cross sections were found to increase with increasing charge state of the precursor anion. The experimental findings are supported by the calculations of the total electron capture cross sections, based on the classical over-the-barrier model, restricted to a simple uniformly charged linear protein structure and a near-end electron capture.